Improving lung function capacity in patients with chronotropic incompetence using closed loop stimulation: A randomized crossover study - Chen, Wen-Ling; Chen, Lung-Ching; Hsu, Pei-Sung; Shyu, Kou-GI; Hung, Huei-Fong; Lee, Shih-Huang; Wang, Tzu-Lin; Lai, Wei-Ting; Chen, Kuan-Jen; Liao, Zhen-Yu; Chuang, Cheng-Yen; Chou, Ching-Yao; et al. (Journal of the Formosan Medical Association, 2025)
Chronotropic incompetence (CI) severely limits exercise tolerance due to impaired heart rate responses. This study investigated whether pacemaker with closed-loop stimulation (DDD-CLS) pacing, which provides rate acceleration in response to exertion, could enhance lung function and cardiopulmonary capacity compared pacemaker without CLS pacing in patients with CI. This randomized crossover trial included 32 patients with CI who were compared to each CLS and DDD pacing over 2 months. Spirometry was used to assess the forced vital capacity (FVC). Cycling-based cardiopulmonary exercise testing (CPET) measured peak oxygen uptake (peak VO2). DDD-CLS pacing yielded significantly higher FVC (2.2 ± 0.8 L) versus DDD pacing (2.0 ± 0.7 L), p = 0.036, a 3.2% improvement. Moreover, those in the DDD-CLS mode showed a significantly higher FEV1 of 1.8 ± 0.6 L compared to the DDD mode of 1.7 ± 0.5 L (p = 0.03). Compared with DDD pacing, DDD-CLS pacing also achieved superior peak VO2 (14.9 ± 4.0 vs 12.2 ± 3.7 mlO2/kg/min, p < 0.001) and peak heart rate (106.9 ± 9.7 vs 98.3 ± 19.8 bpm, p = 0.013). DDD-CLS and DDD pacing modes showed significant correlations between FVC and peak VO2 and between peak VO2 and peak heart rate during CPET. Compared with DDD mode, DDD-CLS pacing provided physiological chronotropic support to improve cardiopulmonary function during exertion, which enhanced lung capacity in patients with CI.